Struktur Tematik Berita Judi Online Pada Media Detik.Com (Analisis Wacana Kritis Teun A. Van Dijk) - Zulfi, Bitran Tony Awaldi; Wibowo, Imam Suwardi; Yusra, Hilman (Universitas Negeri Padang, 2024)
This study aims to describe the thematic structure in online gambling news on detik.com media using critical discourse analysis theory from the perspective of Teun A. Van Dijk to see how journalists utilize thematic structures in the form of topics and subtopics in producing a discourse. This research was conducted on the online news portal detik.com which discussed the topic of online gambling published in December 2023. The data in this study were obtained using documentation techniques and reading and writing techniques by attaching screenshots of 13 (thirteen) news texts contained in the detik.com online media. The results of this study show that journalists always use thematic structures or global meanings in the form of topics and subtopics that have mutual coherence to convey ideologies or thoughts contained in the main topic of news through several subtopics raised by including existing facts.Kata Kunci: Analisis Wacana, Berita Online